Mobile Based Application Design of Management System “Travel Budget” Using Flutter - Maziya Azelicha Ayana; Suwarno Liang (Universitas Internasional Batam, 2024)
Nowadays, many people participate in traveling as their preferred leisure activity. When traveling, unexpected circumstances can arise, including changes in travel plans, unforeseen expenses, medical costs, or alterations to meal plans, which may require additional budgeting. Recording expenses during a trip allows travelers to allocate their budget effectively for transportation, food, lodging, tourist activities, and other expenses. To solve this problem, this study aims to design a mobile management system called